(untitled) (Research, Society and Development, 2020)
Objective: To analyze the distribution of vaccine doses against HPV in children and teenagers between nine and fourteen years old in a public school in the city of Campina Grande – PB. Methods: It is a descriptive and exploratory research, with a quantitative approach. The sample was composed by 81 children and teenagers, considering the immunized and unimmunized. In order to collect the data, a quiz was applied; the collected data was grouped and organized through spreadsheets; statistically analyzed through simple descriptive statistics, represented in tables and had posterior inference from the relevant scientific literature. Results: 70,4% of the children and teenagers were already vaccinated; 68,4% present the full vaccination schedule; 91,2% already heard about HPV; 63,1% believe it is a virus and that the main reason for the vaccine’s non-adherence by the target population is that they could not attend to the basic health unit (29,2%). Conclusion: It was evidenced that the distribution of vaccine doses against HPV is in a regular situation, since more than half of the people who partipated in the study were vaccinated and present the full vaccination schedule. It is notorious that the great majority of the target population has satisfactory knowledge on the Human Papillomavirus (HPV) and the impossibility to go to the basic health care unit interfered with vaccine adherence.